2013
DOI: 10.2478/s11756-013-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposition of antitumour activity of a chemically characterized exopolysaccharide from a probiotic Lactobacillus plantarum MTCC 9510

Abstract: As majority of chemical compounds identified as anti-cancerous are toxic to normal cells, the discovery and identification of new safe drugs is a necessity in the biomedical field. The antioxidant, antitumour and immunomodulating properties of an exopolysaccharide of sequence -α-D-glucose, α-D-mannose and β-D-glucose-, purified from a probiotic Lactobacillus plantarum was studied. The immunostimulation of the compound in human lymphocytes was seen at a concentration of 0.1 mg/mL with 20% proliferation rate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 27 publications
(29 reference statements)
1
22
0
1
Order By: Relevance
“…The cytotoxic effect of l-EPSs obtained from L. delbrueckii ssp. bulgaricus B3, and L. plantarum GD2 strains on SH-SY5Y cells was in line with the literature 67,68 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The cytotoxic effect of l-EPSs obtained from L. delbrueckii ssp. bulgaricus B3, and L. plantarum GD2 strains on SH-SY5Y cells was in line with the literature 67,68 .…”
Section: Resultssupporting
confidence: 90%
“…bulgaricus B3, and L. plantarum GD2 strains on SH-SY5Y cells was in line with the literature 11,12 . l-EPSs at different concentrations alone did not cause any apparent cytotoxicity (data not shown). Ismail and Nampoothiri 67 reported that 50 mg/mL EPS obtained from L. plantarum MTCC 9510 strain had a cytotoxic effect on normal fibroblast cells (L929) at 60%. Dilna et al 68 , according to the study, the EPS obtained from L. plantarum RJF4 strain at a concentration of 500 µg/mL normal fibroblast cells (L6) on the 35% cytotoxic effect was determined.…”
Section: Resultsmentioning
confidence: 99%
“…). Furthermore, this strain produces an exopolysaccharide (Ismail and Nampoothiri ), which is well characterized (Ismail and Nampoothiri ) and exhibits anticancer property (Ismail and Nampoothiri ).…”
Section: Introductionmentioning
confidence: 99%
“…The rational for selecting L. plantarum MTCC 9510 for this study is due to its probiotic attributes which are well established (Aswathy et al 2008). Furthermore, this strain produces an exopolysaccharide (Ismail and Nampoothiri 2010), which is well characterized (Ismail and Nampoothiri 2013) and exhibits anticancer property (Ismail and Nampoothiri 2014).…”
mentioning
confidence: 99%
“…Researches revealed that these glycosidic components generally are less cytotoxic toward normal cells which makes them a promising candidate in cancer therapy [13,36,37]. In this regard, we carried out experimental assays for evaluating the possible modulatory role of L. paracasei EPS on the molecular targets involved in cancer cell growth, apoptosis, survival, and inflammation signaling pathways.…”
Section: Discussionmentioning
confidence: 99%